Early vasopressor use following traumatic injury: a systematic review. Issue 11 (17th November 2017) - Hylands, Mathieu; Toma, Augustin; Beaudoin, Nicolas; Frenette, Anne Julie; D'Aragon, Frédérick; Belley-Côté, Émilie; Charbonney, Emmanuel; Møller, Morten Hylander; Laake, Jon Henrik; Vandvik, Per Olav; Siemieniuk, Reed Alexander; Rochwerg, Bram; et al.
Abstract : Objectives: Current guidelines suggest limiting the use of vasopressors following traumatic injury; however, wide variations in practice exist. Although excessive vasoconstriction may be harmful, these agents may help reduce administration of potentially harmful resuscitation fluids. This systematic review aims to compare early vasopressor use to standard resuscitation in adults with trauma-induced shock. Design: Systematic review. Data sources: We searched MEDLINE, EMBASE, ClinicalTrials.gov and the Central Register of Controlled Trials from inception until October 2016, as well as the proceedings of 10 relevant international conferences from 2005 to 2016. Eligibility criteria for selecting studies: Randomised controlled trials and controlled observational studies that compared the early vasopressor use with standard resuscitation in adults with acute traumatic injury. Results: Of 8001 citations, we retrieved 18 full-text articles and included 6 studies (1 randomised controlled trial and 5 observational studies), including 2 published exclusively in abstract form. Across observational studies, vasopressor use was associated with increased short-term mortality, with unadjusted risk ratios ranging from 2.31 to 7.39. However, the risk of bias was considered high in these observational studies because patients who received vasopressors were systematically sicker than patients treated without vasopressors. One clinical trial (n=78) was too imprecise to yield meaningful results. Two clinical trials are currently ongoing. No study measured long-term quality of life or cognitive function. Conclusions: Existing data on the effects of vasopressors following traumatic injury are of very low quality according to the Grading of Recommendations, Assessment, Development and Evaluation methodology. With emerging evidence of harm associated with aggressive fluid resuscitation and, in selected subgroups of patients, with permissive hypotension, the alternatives to vasopressor therapy are limited. Observational data showing that vasopressors are part of usual care would provide a strong justification for high-quality clinical trials of early vasopressor use during trauma resuscitation. Trial registration number: CRD42016033437 .